In My Body - Bennett, Sina (East Carolina University)
As a fat woman navigating the complexities of modern society, I am constantly confronted with societal expectations and perceptions of beauty. With this body of work, I wanted to explore the idea of how I feel about myself living in a fat body and how that has affected my mental state. This thesis explores the emotional terrain of living as a fat woman, focusing on the intersection of societal beauty standards, size, and identity. Through a series of ten ceramic sculptures depicting figures in various emotional states, I delve into the complexities of body image and self-perception. Through this body of work, I hope to encourage people to rethink their preconceived notions about body image and encourage greater acceptance of different body types.
Keywords: Figurative Sculpture; Figurative Ceramics; Body Positive; Fat; Fatphobia; Beauty Standards; Clay; Ceramics